Theoretical Framework Development for Supply Chain Risk Management for Malaysian Manufacturing - Muhammad Saeed Shahbaz; Raja Zuraidah RM Rasi; Mohd Hafiz Zulfakar; Md Fauzi Bin Ahmad; Engr Muhammad Mujtaba Asad (International Journal of Supply Chain Management, 2018)
Globalization, rapid technological changes and growing competition not only facilitate but also make the supply chain more complex and fragile. Any disruption can disturb many organizations and even whole system. There are many theories and frameworks that present solution but no study is available that theoretically development framework for supply chain risk management. Due to the lack of structured supply chain risk management system the focus of this study is to develop a novel framework for identifying the potential risks and assessment of their effects on supply chain performance. Additionally, evaluate the role of supply chain collaboration in risk mitigation and performance improvement in Malaysian manufacturing sector. This study has highlighted numerous problems of Malaysian organizations and developed a theoretical framework. This framework will guide Malaysian organizations and will present better understanding for managers in resolving these issues. This is a conceptual paper, systematic as well as content analysis have been done for literature review. For future study, there is need to empirically verification of this theoretical framework. The proposed methodology to achieve this framework is; questionnaire will be developed from a pool and will be validate by exploratory view for risk identification. This questionnaire will be distributed among Malaysian manufacturing and data will be analyzed through Structural Equation Modeling (SEM) for risk assessment and mitigation. The theoretical contribution of this study is support of theory of swift, even flow as underpinning theory and information processing theory as supportive theory.